Socialization of the Utilization of Google Sites as a Promotional Media for Lasak Donuts in Medan City - Atika Aini Nasution; Baginda Harahap (IJCS: International Journal of Community Service, 2022)
This dedication is an attempt to improve the quality of marketing during the pandemic era as a form communication independence. This dedication aims to create Online-based promotional media during a pandemic, as well find out the response to the use of online promotion-based google sites as a promotional medium for Lasak Donuts during the pandemic. This service is a type of development service using the ADDIE model, which has gone through the validation stage by involving three validators namely (material experts, media experts promotion and IT experts), then use response involves visitors and consumers. Based on the results of the service of material experts, media promotion experts and IT experts are considered very good with the average value of material experts is 88%, media promotion experts are 89%, IT expert 96%. Visitor and consumer response to usage learning media google sites are very good criteria with get an average teacher score of 98% and students 84%. It can be concluded that the Use of Google Sites is Online Based learning as a promotional medium for Lasak donuts is stated to be very good with usage responses positive as a learning medium during a pandemic.